Normal saline nasal irrigation in childhood allergic rhinosinusitis: Our experiences in a tertiary care teaching hospital of Eastern India - Swain, Santosh Kumar; Behera, Ishwar Chandra; Das, Alok; Mohanty, Jatindra Nath (Indian Journal of Child Health, 2019)
Background: Allergic rhinosinusitis (AR) is a common clinical disorder among pediatric patients. There are different modalities of the treatment for AR ranging from antihistamines, corticosteroids, and mast cell stabilizers in oral or topical formulations. Objective: The objective of the study was to find out the effect of nasal saline irrigation or saline spray for reducing the symptoms in childhood AR along with an oral antiallergic treatment. Materials and Methods: The present study is a prospective study of the children suffering from AR between December 2017 and January 2019. All the children were in the age group of 5–16 years. All were randomly divided into two groups. In Group I, nasal saline irrigation was done in 56 patients twice a day along with an oral antiallergic treatment. Group II or control group consists of 56 children of AR those received only oral antiallergic treatment. Follow-up was done at the 2nd, 4th, 6th, and 8th weeks after treatment and symptom scores were compared with previous clinical presentations. The data were analyzed by applying t-test. Results: Each group had 56 children with a mean age of 12.6 years in Group-I whereas 11.7 years in Group-II. The percentage disability scores (PDSs) at the beginning of the study were comparable in both the groups (83% vs. 88%). Both groups showed improvement in the PDS after treatment at the 2nd week; however, it was more in Group-I than in Group-II (p<0.001, paired t-test). Conclusion: Involvement of normal saline irrigation with oral antiallergic treatment in the present study provided satisfactory symptomatic relief in comparison with antiallergic treatment in pediatric patients suffering from AR.